2022
DOI: 10.3389/fradi.2022.1033521
|View full text |Cite
|
Sign up to set email alerts
|

MRI visibility and displacement of elective lymph nodes during radiotherapy in head and neck cancer patients

Abstract: Background and purposeTo decrease the impact of radiotherapy to healthy tissues in the head and neck region, we propose to restrict the elective neck irradiation to elective lymph nodes at risk of containing micro metastases instead of the larger lymph node volumes. To assess whether this new concept is achievable in the clinic, we determined the number, volume changes and displacement of elective lymph nodes during the course of radiotherapy.Materials and methodsMRI scans of 10 head and neck cancer (HNC) pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 24 publications
1
3
0
Order By: Relevance
“…The number of detected elective lymph nodes in this study was similar to a previous study that examined the MRI visibility and displacement of lymph nodes during radiotherapy in HNC patients (level Ib: 5 vs. 5, level II: 18 vs. 21, level III: 8 vs. 11, level IV: 2 vs. 7 and level V: 6 vs. 8) [15] . Pathology studies that investigated neck dissections in HNSCC patients reported a lymph node yield varying from 34 to 46 [18] , [19] , [20] , [21] on each side of the neck, which is higher than the number of lymph nodes seen in the present study.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…The number of detected elective lymph nodes in this study was similar to a previous study that examined the MRI visibility and displacement of lymph nodes during radiotherapy in HNC patients (level Ib: 5 vs. 5, level II: 18 vs. 21, level III: 8 vs. 11, level IV: 2 vs. 7 and level V: 6 vs. 8) [15] . Pathology studies that investigated neck dissections in HNSCC patients reported a lymph node yield varying from 34 to 46 [18] , [19] , [20] , [21] on each side of the neck, which is higher than the number of lymph nodes seen in the present study.…”
Section: Discussionsupporting
confidence: 87%
“…However, the differences in diameter of lymph nodes in level II were small and therefore not deemed clinical relevant. It is known that lymph nodes decrease in size during radiotherapy treatment [15] as lymphatic tissue is sensitive to radiation [22] . However, the results of this study indicate that this effect is not already visible in the first week of treatment.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations